2011
DOI: 10.1002/jmv.22134
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response and avidity of respiratory syncytial virus‐specific total IgG, IgG1, and IgG3 in young children

Abstract: Respiratory syncytial virus (RSV) is a major cause of acute respiratory disease in infants and young children. Considering that several aspects of the humoral immune response to RSV infection remain unclear, this study aimed to investigate the occurrence, levels, and avidity of total IgG, IgG1, and IgG3 antibodies against RSV in serum samples from children ≤5 years old. In addition, a possible association between antibody avidity and severity of illness was examined. The occurrence and levels of RSV-specific I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
3
22
1
Order By: Relevance
“…In addition, the estimated slope between k d and NT was significantly different from 4 to 6 months old group to 7–12 months old group ( p  = 0.0042), and from 13 to 18 months old group to 19–36 months old group ( p  = 0.0006). These findings are well consistent with results of previous studies showing that the age-dependent antibody affinity maturation plays an important role in protection from viral infections (Delgado et al, 2009, Freitas et al, 2011, Meurman et al, 1992).
Fig.
…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the estimated slope between k d and NT was significantly different from 4 to 6 months old group to 7–12 months old group ( p  = 0.0042), and from 13 to 18 months old group to 19–36 months old group ( p  = 0.0006). These findings are well consistent with results of previous studies showing that the age-dependent antibody affinity maturation plays an important role in protection from viral infections (Delgado et al, 2009, Freitas et al, 2011, Meurman et al, 1992).
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…A past clinical study focused on the comparison of levels of RSV-specific IgG1 and IgG3 in patients, and its results suggested that the avidity of IgG1 against the whole RSV protein correlates with the protection against RSV infection in infants < 3 months old. The correlation between avidity of IgG3 and protection against RSV infection was hardly characterized because of lower concentrations of IgG3 as compared with IgG1 (Freitas et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Maternally-derived high affinity RSV-specific serum IgG antibody is the best known correlate of protection against infection in infants (Fig 2d) and it is assumed that the relative rarity of severe RSV disease in the first weeks of life is due to virus-specific maternally derived antibody 44,45,[63][64][65][66][67] . However, some of this protection may be indirect, due to reduced rates of maternal infection in those with high levels of antibody.…”
Section: Rsvmentioning
confidence: 99%
“…Nevertheless, severe RSV infection is consistently associated with low levels of pre-existing serum or cord blood RSV antibody 44,45,[63][64][65][66][67] . Infants in the top .…”
Section: Rsvmentioning
confidence: 99%
“…Infants below three months of age still have considerable amounts of maternal RSV-specific antibodies [3]. The current consensus about the role of antibodies during RSV pathogenesis is that antibodies are protective, as most studies report that high levels of neutralizing maternal antibody titers are associated with protection against RSV infections [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%